1992
DOI: 10.1016/0032-3861(92)91114-h
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium tetroxide staining of polybutylene terephthalate (PBT) and polyisobutylene-b-PBT segmented block copolymers

Abstract: A ruthenium tetroxide (RuO4) staining method has been evaluated for segmented polyisobutylene-bpolybutylene terephthalate (PIB-b-PBT). Solution cast films and melt pressed samples have been studied. For comparison PBT has also been studied. PBT and PIB-b-PBT could be stained with RuO4 at room temperature. The observed structures on the PBT and PIB-b-PBT films were spherulitic with lamellae. In some regions in the PIB-b-PBT films large scale phase separation was observed. In the melt pressed PIB-b-PBT samples t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Preparative methods for TEM specimens and morphological results are summarized in Table 1 in comparison with those by Janik et al [13].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preparative methods for TEM specimens and morphological results are summarized in Table 1 in comparison with those by Janik et al [13].…”
Section: Methodsmentioning
confidence: 99%
“…As is summarized in Table 1, Janik et al [13] reported on RuO 4 -staining of solvent-cast thin films of PBT and its copolymers that were subjected directly to TEM observations after the staining was done at room temperature for 15 min to 5 h and at 75°C for 3 h. They also prepared a TEM specimen by RuO 4 -staining of surface obtained by trimming a given meltpressed sample and then ultrathin-sectioning at room temperature, where the staining was done by suspending the sample in aqueous RuO 4 solution for 24 h at room temperature or 16 h at 75°C. It is noted that RuO 4 stained the very thin cast PBT film at room temperature while good quality images were obtained only from the melt-pressed specimen stained at 75°C for 15 h. On the other hand, the copolymer sample with a lower crystallinity was successfully stained at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…12 In Montezinos et al's study, the fresh mixture was dark red in color and should be used immediately inasmuch as it would deteriorate within a few hours. In Janik et al's work, the solution was olive green, and if the container was quickly sealed, the solution could stay green for up to 72 h at room temperature.…”
Section: Staining Agent and Processmentioning
confidence: 97%
“…18 This modificarial from the polymer section, whereas black parts indition of the conventional ruthenium staining techcate a local thickening of the cut due to excess of crystalnique 19 already proved its versatility by successful apline material. Nevertheless, the study of unstained secplications for polyolefines, 18,20,21 polyesters and their tions shows that the resolution of white parts does not blends, 22,23 and poly(oxymethylene). 24 allow to explore with certainty the subfibrillar traits, while the too faint contrast of the black parts necessites to be enhanced.…”
Section: 2mentioning
confidence: 97%